Historicizing Roma in Central Europe : between critical whiteness and epistemic injustice - Shmidt, Victoria R.; Jaworsky, Bernadette N. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"In Central Europe, limited success in revisiting the role of science in the segregation of Roma reverberates with the yet-unmet call for contextualizing the impact of ideas on everyday racism. This book attempts to interpret such a gap as a case of epistemic injustice. It underscores the historical role of ideas in race-making and provides analytical lenses for exploring cross-border transfers of whiteness in Central Europe. In the case of Roma, the scientific argument in favor of segregation continues to play an outstanding role due to a long-term focus on the limited educability of Roma. The authors trace the long-term interrelation between racializing Roma and the adaptation by Central European scholars of theories legitimizing segregation against those considered non-white, conceived as unable to become educated or "civilized." Along with legitimizing segregation, sterilization and even extermination, theorizing ineducability has laid the groundwork for negating the capacity of Roma as subjects of knowledge. Such negation has hindered practices of identity and quite literally prevented Roma in Central Europe from becoming who they are. This systematic epistemic injustice still echoes in contemporary attempts to historicize Roma in Central Europe. The authors critically investigate contemporary approaches to historicize Roma as reproducing whiteness and inevitably leading to various forms of epistemic injustice. The methodological approach herein conceptualizes critical whiteness as a practice of epistemic justice targeted at providing a sustainable platform for reflecting upon the impact of the past on the contemporary situation of Roma."--
Whiteness: a locus for doing race -- Obscure racism: from national indifference to whitening Roma -- The post-socialist shift in pathologizing: from disabled Roma to disabled socialism -- The limits and options of historical narratives concerning Roma in Central Europe -- The inception of whiteness: the Grellmannian intersections of European Roma -- Global racial order comes to Central Europe: the puzzle of "white gypsies" at the dawn of the twentieth century -- The institutionalization of a racialized approach to Roma in the 1920s-1940s: rooting the stigma of an insecure population -- In (re)search of inclusion: Roma under the pressure of de-historicizing between the 1950s and 1990s
OCLC-licensed vendor bibliographic record.
Keywords: Romanies -- Europe -- Ethnic identity; Romanies -- Cultural assimilation -- Europe; Romanies -- Civil rights -- Europe -- History; Race discrimination -- Europe -- History; Romanies -- Europe -- Social conditions; Europe -- Race relations -- History; HISTORY / General; HISTORY / Europe / Eastern; HISTORY / Europe / Former Soviet Republics